Modern bargello : how to stitch 15 colourful projects - Francis, Tina (Search Press Ltd., 2020)
Bargello stitching is making a comeback with modern crafters. Famous for its flame-like stitches that are as traditional as they are modern, bargello is quick to master, fast to achieve and, beware, very addictive. Bargello stitching, or Florentine, was in its heyday in the seventies and it's becoming popular again with modern crafters. There is a project for everyone, whether you are new to bargello, or are an original bargello fan. Tina Francis shows you how to combine bold, bright colours in attractive, almost psychedelic patterns to create the illusion of 3-D. Use her easy-to-follow patterns and approachable instructions to master appealing designs, then turn your creations into wearables and interiors that look as much at home in modern houses as in traditional stately homes. Try a floor cushion, a lampshade, a wall hanging, a brooch or a pincushion. Hard to choose? Make them all! Bargello is easy to master, quick to achieve and very addictive. The stitches take on a rhythm of their own which makes it extremely relaxing and before long you'll be measuring your days in inches not hours. With only a handful of materials required - canvas, tapestry wool, tapestry needle, instructions - bargello is certain to become your craft of choice.